Effect of implementation of a smoke-free policy on physical violence in a psychiatric inpatient setting: an interrupted time series analysis. (July 2017) - Robson, Debbie; Spaducci, Gilda; McNeill, Ann; Stewart, Duncan; Craig, Tom J K; Yates, Mary; Szatkowski, Lisa
Summary: Background: Smoke-free policies are important to protect health and reduce health inequalities. A major barrier to policy implementation in psychiatric hospitals is staff concern that physical violence will increase. We aimed to assess the effect of implementing a comprehensive smoke-free policy on rates of physical assaults in a large UK mental health organisation. Methods: We did an interrupted time series analysis of incident reports of physical assault 30 months before and 12 months after the implementation of the policy in the inpatient wards of South London and Maudsley National Health Service Foundation Trust, London, UK. We used a quasi-Poisson generalised additive mixed model to model the monthly incidence of physical assaults as a function of several explanatory variables. Findings: 4550 physical assaults took place between April 1, 2012, and Sept 30, 2015; 225 (4·9%) of which were smoking-related. After adjustment for temporal and seasonal trends and key confounders (sex, age, schizophrenia or related disorders, or having been sectioned under the Mental Health Act), there was a 39% reduction in the number of physical assaults per month after the policy introduction compared with beforehand (incidence rate ratio 0·61, 95% CI 0·53–0·70; p<0·0001). Interpretation: Introduction of a comprehensive smoke-free policy appeared to reduce the incidence of physical assaults. Adequately resourced smoke-free policies could be part of broader violence reduction strategies in psychiatric settings. Funding: National Institute for Health Research Collaboration for Leadership in Applied Health Research and Care South London (King's College Hospital NHS Foundation Trust).